Self-Efficacy and Test Anxiety as Predictors of Achievement in Uni-Dimensional Mathematics Objectives Test: A Study of Secondary School Students in Calabar, Nigeria - Ayang, Ethelbert E.; Ngwu, Ukam Ivi (EDUMALSYS Journal of Research in Education Management, 2025)
This study examined the influence of self-efficacy and test anxiety on mathematics achievement among Senior Secondary School One (SSSI) students in Calabar Metropolis, Cross River State, Nigeria. An ex post facto research design was adopted, involving a sample of 309 students selected through stratified random sampling. Data were collected using a structured questionnaire and a standardized Uni-Dimensional Mathematics Objectives Test. Two hypotheses were tested using the One-Way ANOVA statistical technique. Results indicated that self-efficacy had a significant positive impact on students’ achievement in mathematics, while test anxiety was found to significantly impair mathematical performance. The findings underscore the importance of psychological factors in academic success and highlight the need for interventions at both the instructional and institutional levels. The study recommends that educators implement teaching strategies that bolster students’ self-efficacy while minimizing test anxiety. Furthermore, schools are advised to introduce structured programs targeting anxiety reduction, such as relaxation techniques, mindfulness practices, and effective test-taking strategies. These measures are essential for enhancing mathematics achievement and overall academic outcomes in senior secondary education.